EFFECT OF FERTILIZATION, ROOTSTOCKS AND GROWTH STIMULANT ON GROWTH OF Citrus limon L. SAPLING. - & Khalil, Alkhafaji; & Khalil, Alkhafaji (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A research  was  carried out in the lath house of the College of Agricultural Engineering sciences / University of Baghdad / Al-Jadriyah,  for three growth seasons Spring 2017, Fall 2017 and Spring 2018 to study the effect of different fertilization methods, were Fertigation (Ft) , Foliar application (Fa), traditional soil fertilization (Fo) and growth stimulant with two concentrations 0 (D0) and 1.5 mg.L-1 (D1)  on the growth of local Citrus limon L. Saplings grafted on Citrus aurantium L. (So), C. volkameriana  (Vo), and Citrumello (Co). Saplings were cultivated in 10 kg plastic containers. A factorial experiment was carried out according to the Nested-Factorial Experimental design. Results indicated foliar application (Fa) superiority, followed by  Fertigation (Ft) in plant height, rootstock and scion diameter, while the number of  shoots  increased significantly using (Ft). Lemon trees grafted on (So) showed superiority in plant height, while trees grafted on (Vo) recorded higher rates in rootstock, scion diameter, and shoot  number. Plants fertilized with (Fa) surpassed in nutrient use efficiency (NUE) of  N, P, K  they were 1.18, 0.43 and 1.30 g.dw -1, respectively. (Vo) indicated highest value in (NUE) of  N, P, K elements in plants (1.32, 0.48 and 1.45 g. dw -1) in comparison  to So and Co. The Fa * Vo * D0 treatment  increased significantly  rootstock stem diameter (73.15 and 126.03%), while  the  highest rate in plant height was recorded by Fa * So* D0 (111.19%.)  The highest increase rate of shoot number (483.9%), was by Ft * So * D1. The treatment  Fo * Co * D1, gave the  highest carbohydrate (4.92%).